2018
DOI: 10.1002/asia.201800199
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Imidazoliumyl‐Substituted Phosphorus Compounds

Abstract: This review aims to highlight the recent developments in the chemistry of selected imidazoliumyl-substituted phosphorus compounds. The synthetic approaches for their preparation with phosphorus in various oxidation states and coordination environments are discussed. Their intriguing properties and versatile chemistry strongly depends on the bonding motif at the P atoms, which is given special focus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 160 publications
(292 reference statements)
0
21
0
2
Order By: Relevance
“…[19] For transferring an NHC/cAAC [cAAC = cyclic (alkyl)(amino)carbene]s tabilized phosphorus-atom manifold, different strategies have provens uccessful, although certainly none of them is universally applicable, but rather limited to special substrates. Tamm and co-workersu sed ap hosphinidene bearing at rimethylsilyl (SiMe 3 )s ubstituent that enableda Me 3 SiCl elimination. Thus, the synthesis of transition-metal-substitutedp hosphinidenes was available.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[19] For transferring an NHC/cAAC [cAAC = cyclic (alkyl)(amino)carbene]s tabilized phosphorus-atom manifold, different strategies have provens uccessful, although certainly none of them is universally applicable, but rather limited to special substrates. Tamm and co-workersu sed ap hosphinidene bearing at rimethylsilyl (SiMe 3 )s ubstituent that enableda Me 3 SiCl elimination. Thus, the synthesis of transition-metal-substitutedp hosphinidenes was available.…”
mentioning
confidence: 99%
“…[20] The complexes[ SnCl 2 (SIMes)] (1b)a nd [PbBr 2 (SIMes)] (1c)w ere used as tin(II) and lead(II) sources, respectively (Scheme 1). [21,22] Subsequentr eactions of compounds 1a-c with SIMesPK at lowt emperatures (À78 8C) yielded K[(SIMesP) 3 E] (E = Ge: 2;Sn: 3,Pb: 4)ashighly sensitive towardso xygen and moisture, red crystallines olids. These compounds are best described as Group 14 ate complexes, in which the cation is coordinated by the p-systemo ft he mesityl substituents.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Es war sehr überraschend, dass selbst bei À80 8 8C nur ein leicht verbreitertes,bei À62.9 ppm zentriertes Singulett im 31 2 As] + in 4b ist das erste strukturell charakterisierte Beispiel eines doppelt NHC-substituierten As I -Kations und das zweite in der Literatur erwähnte. [8,16] Interessanterweise wurde das einzige andere bekannte Beispiel von Märkl et al über die Reaktion von 2-Chlor-N-Methyl-Benzthiazolium-Tetrafluoroborat mit As-(SiMe 3 ) 3 hergestellt. [17] Die Molekülstruktur von 4b ist in Abbildung 2d argestellt.…”
Section: Angewandte Chemieunclassified
“…This adduct was subsequently used for the preparation of the corresponding parent phosphinidene adduct (IDipp)PH, which was also isolated by Grützmacher et al from the reaction of corresponding imidazolium chloride salt with the phosphorus cage complex P 7 (SiMe 3 ) 3 or with sodiumphosphaethynolate Na(OCP) . Several other groups have also developed new synthetic procedures for the isolation of numerous carbene‐phosphinidene adducts and those examples were summarized in recent reviews, Both theoretical and experimental investigations revealed that NHC‐phosphindenes can be regarded as inversely polarized phosphaalkenes as illustrated by the resonance structures A , B presented in Chart .…”
Section: Introductionmentioning
confidence: 99%